The students’ perceptions of the English programs at a pilot academy in Indonesia - UtamiMinerva Daneya; Berliana Winny (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
This research aims to explore and investigate the students’ perceptions of English Programs held by the Academy and find out about the implementation of the Programs. The students were asked to respond to a questionnaire about how they perceived the programs to help them pass the TEP. The questionnaire was distributed to obtain information about five areas related to achieving program objectives and student improvement in these four skills. The results show that the participants viewed the English programs as effective in improving their English competencies. However, they also led to some deficiencies which seem to be related to the program’s implementation. Regarding these deficiencies, the researcher recommends conducting further studies on other aspects of the programs, such as methods and tools in implementing the programs and the instructors’ point of view in the academy.